2016
DOI: 10.1542/hpeds.2015-0198
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Reduced Pulse Oximetry Use on Alarm Frequency

Abstract: Reducing continuous pulse oximetry use alone may not make substantial reductions in overall alarm counts. Even on our intervention unit, alarm burden remained quite high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…40 In a secondary analysis of a prior quality improvement project 41 aimed at reducing the time using pulse oximetry in patients with wheezing illnesses, Schondelmeyer et al found no difference in overall alarm frequency despite a significant decrease in pulse oximetry use. 42 However, significant reductions in pulse oximetry use occurred in both the intervention and control hospital units in this single centre study. Given that monitors cannot alarm when they are off, future studies examining the effects of pulse oximetry reduction are likely to demonstrate an impact on alarm frequency and fatigue.…”
Section: Overdiagnosis and Harmmentioning
confidence: 62%
“…40 In a secondary analysis of a prior quality improvement project 41 aimed at reducing the time using pulse oximetry in patients with wheezing illnesses, Schondelmeyer et al found no difference in overall alarm frequency despite a significant decrease in pulse oximetry use. 42 However, significant reductions in pulse oximetry use occurred in both the intervention and control hospital units in this single centre study. Given that monitors cannot alarm when they are off, future studies examining the effects of pulse oximetry reduction are likely to demonstrate an impact on alarm frequency and fatigue.…”
Section: Overdiagnosis and Harmmentioning
confidence: 62%
“…In 2 previous studies, in which IPO was initiated after patients were completely weaned off oxygen, researchers did not detect a difference in need for transfer to a higher level of care in nonhypoxemic patients; however, these studies did not reveal a decrease in LOS. 6,9 In a recent review of pulse oximetry in bronchiolitis, Quinonez et al 14 point to extensive evidence of "overdiagnosis of hypoxemia" in infants with bronchiolitis and list several potential harms from this overdiagnosis, including prolongation of hospital stay. These authors speculate that previous studies did not reveal a decrease in LOS with the use of IPO because the "intervention was not initiated until children were weaned off oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…6 The perceived need for supplemental oxygen based on pulse oximetry readings is a primary driver of prolonged length of stay (LOS) in admitted bronchiolitis patients. 7,8 Although previous studies have not revealed a reduction in hospital LOS for bronchiolitis 6 or time to readiness for discharge in a heterogeneous group of wheezing patients, 9 judicious use of IPO in nonhypoxemic patients has been shown to be safe and with no detectable difference in the need for care escalation 6 or the rate of adverse events. 9,10 Bronchiolitis is a common reason for hospitalization to our inpatient unit, accounting for almost half of our admissions in the winter.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Although the authors of previous studies did not show significant reduction in overall alarm counts when targeting CPO alone, our efforts to improve the appropriate use of pulse oximetry in children with mild-tomoderate bronchiolitis resulted in decreased clinical SpO2 alarms, which, when not indicated, can interrupt care and cause noise pollution and alarm fatigue. 14,15 Our ability to engage multiple stakeholders, including residents, contributed to the success of the project. Although the project took place on a small unit over a limited period of time, we are encouraged by our experience and anticipate continued resident involvement moving forward to sustain change.…”
mentioning
confidence: 99%